Implementation of the Madrasah Digital Report Information System Management (RDM) in Learning Evaluation - Alfiyatun Alfiyatun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The advancement of information technology encourages madrasas to adopt digital systems in the management of academic data, one of which is the Digital Report Card of Madrasah (RDM) that is expected to improve the efficiency, accuracy, and effectiveness of learning evaluation. This study aims to analyze the implementation of the management of the Digital Report Card of Madrasah (RDM) at MAN 1 Pangandaran, including policies, implementation practices, successes, challenges, and its impact on learning evaluation. The method used in this research is descriptive qualitative, with data collection techniques through observation, interviews, and documentation with the head of the madrasa, teachers, operators, and class guardians. The results of the study indicate that the use of RDM is technically in accordance with the guidelines and facilitates the assessment process, but has not fully achieved its main objectives due to user adaptation challenges, infrastructure limitations, and human resource readiness. It can be concluded that RDM brings positive innovation to the learning evaluation system, but its effectiveness depends on resource readiness and infrastructure support. Continuous improvement and intensive training are needed so that the potential of RDM in enhancing the quality of education in madrasas can be maximized.